PSYCHOLOGICAL FACTORS OF THE FORMATION OF COGNITIVE NEEDS ОF STUDENTS WITH A LOW LEVEL OF MASTERY - Feruzakhon Khabibullo kizi Muminjonova (Journals Park Publishing, 2023)
The article analysis the study of psychological factors underlying the formation of cognitive learning strategies and the factors influence the psychology of university students may provide valuable information to inform the development of intervention programs and targeted learning activities.
Keywords: psychological factors, university students, emotional intelligence, anxiety, empathy, learning strategies, cognitive strategies, educational activities.